Nucleon-nucleon short-range correlations: A hidden driver in binary neutron star inspiral gravitational waves - Bin Hong; Tongqi Liang; Zhongzhou Ren (Physics Letters B, 2025)
Nucleon-nucleon short-range correlations (SRCs) describe the formation of nucleon pairs with high-momentum components, representing an essential issue in nuclear physics, yet their implications for inspiral gravitational waves remain underexplored. In this study, we employ three different nucleon-nucleon SRC models in neutron star interiors to assess their effects on gravitational waves during binary neutron star (BNS) inspiral phase. Our findings indicate that SRC-affected BNS systems exhibit lower gravitational wave frequencies, with a characteristic reduction of approximately 200 Hz compared to the traditional BNS systems. Additionally, SRCs appear to accelerate the BNS inspiral process, leading to a shorter retarded time and notable deviation in the gravitational waveform. These results underscore the critical role of SRC in shaping the features of inspiral gravitational waves and propose that inspiral gravitational waves could potentially serve as an effective probe for detecting SRC phenomena within neutron stars.